Peningkatan Produktivitas Domba melalui Pembinaan Kelompok Peternak Domba Desa Pamulihan terkait Keterampilan Manajemen Pemeliharaan - Ken Ratu gharizah Alhuur; An An Nurmeidiansyah; Denie Heriyadi; Diky Ramdani; Iin Susilawati (Fakultas Peternakan, Universitas Padjadjaran, 2023)
Education regarding the management of sheep rearing in groups of sheep breeders in Pamulihan Village is carried out as a form of effort to increase the productivity of sheep owned by breeders. This educational activity was carried out in Pamulihan Village with an audience of 30 people who are sheep breeders from that village. Educational activities are carried out using the method of delivering material and discussion an evaluating it from pretest and posttest data taken before and after the material delivery session is carried out. Based on the results of the pretest and posttest evaluations, it was found that there was an increase in knowledge about feed management by 22% (from 70% to 92%), planning and recording by 45% (from 40% to 85%), maintenance management by 15% (from 75% to 90%) and Health management as much as 30% (from 60% to 90%). Aspects of the farmer's attitude after participating in the training as much as 90% of the farmers are aware of the deficiencies in the implementation of their farms and 10% are still unsure. In contrast, the desire of the breeders to apply the knowledge gained to their farms is found that 80% of the farmers will implement it, 7% do not, and 13% are doubtful -hesitant. This educational activity succeeded in increasing the knowledge and awareness of breeders in running their farms well. However, it still needs to be given technical examples that are easy for breeders to implement.Â